Rhodium‐Catalyzed Enantioselective Defluorinative α‐Arylation of Secondary Amides. (8th November 2018) - Jang, Young Jin; Rose, Daniel; Mirabi, Bijan; Lautens, Mark
Abstract: We exploited the reactivity of an electronically biased Michael acceptor to perform a defluorinative α‐arylation reaction using a chiral diene(L*)‐rhodium catalyst. Through this methodology, we are able to obtain various secondary amides, containing a tertiary α‐stereocenter and a β, γ‐unsaturated gem ‐difluoro olefin, with excellent enantioselectivities. This methodology addresses the limitations of the previously described α‐arylation methods to construct stereo‐labile tertiary α‐stereocenters. Further investigation of the reaction via in situ 19 F NMR monitoring suggests that the formation of the product leads to the inhibition of the active rhodium catalyst.